PENERAPAN HARGA POKOK PROSES SEBAGAI DASAR PENENTUAN HARGA JUAL PRODUK DENGAN METODE VARIABLE COSTING - Mispiyanti, Mispiyanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2014)
Determining the cost of production in this method the company produces a single product and product types are standard. There are two common methods used is the weighted average cost method and the method of fist in fist out (FIFO). In calculating the cost elements in the cost of production, there are several approaches that a full costing and variable costing. with the research conducted by the author should not apply a mark up percentage is too high, due to the higher mark up the higher the selling price targets. So that the product can not compete in the market because the price is too high. Keywords: Cost of Production, Cost of Prosess and Product Selling Price